L’échéance des Jeux Olympiques de 2016 et les stratégies de restructuration du transport métropolitain de Rio de Janeiro - Antoine Beyer (Confins)
Reorganizing public transport in the metropolitan region of Rio de Janeiro ahead of the Summer Olympic Games 2016.Public transportation played a decisive role in Rio de Janeiro’s bid to host the Summer Olympic Games 2016. To convince the CIO, the local authorities have promised a radical overhaul if the current transport infrastructure. The ambitious plan will rely on various unfinished projects, which were abandoned to a certain extent due to financing problems. But the primary reason for these unfinished projects is to be found in politicians’ inability to effect changes to the management of public transport, which is then left in the hands of the powerful bus company cartels. The currently infrastructure is gradually less capable of responding to the needs of a metropolis of more than 11 million inhabitants and this contributes to widen the social and geographical imbalances of the city, which then further impacts the current infrastructure making even more fragile. This paradox is even greater when one thinks that Curitiba in the southern part of the country is known as an example of innovation in bus transportation with its famous BRT (Bus Rapid Transit) system that inspired so many cities worldwide and has been adopted by almost all other large Brazilian urban centres. For Rio, the preparation for the Olympic Games 2016 is a big task. Presented as infrastructure investments, the BRT projects will need to connect the sites of the Olympic games as well as promote the emergence of new exchange hubs structuring the future of the city. The big question now is whether the current plans will deliver the required changes to the current infrastructure. This is an uncertain bet, whose result will depend on the redefinition of the power struggle between private transport companies and the public authorities